2014
DOI: 10.17795/jjhr-21877
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Effect of an Ointment Made From a Mixture of Brassica oleracea var, Punica granatum, and Plantago major L Extracts in Rats

Abstract: Background:In Iranian traditional medicine, Punica granatum, cabbage, and plantago have been used to prompt wound healing. The effects of cabbage, Punica granatum, and Plantago in wound healing have been investigated to some extent, but no experimental study has been performed to assess the impact of an ointment containing all these three substances on wound healing. Objectives: The aim of the present study was to evaluate the effect of an ointment prepared from a mixture of cabbage, Punica granatum, and plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Another study has revealed that linoleic acid can increase the production of VEGF in various cell types such as macrophages, and cancer cells (Rodrigues et al, 2016). Furthermore, one of the possible mechanisms for the effect of plantago major L on such conditions is the contractile property of smooth muscles such as vasoconstriction, which is resulted from some of its active compounds (Bazafkan et al, 2014;Nejati et al, 2018). Another mechanism that might be involved is the generation of reactive oxygen species (ROS) that modulate the expression and activity of angiogenic factors and signaling pathways (Asif et al, 2016;Entezari Heravi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has revealed that linoleic acid can increase the production of VEGF in various cell types such as macrophages, and cancer cells (Rodrigues et al, 2016). Furthermore, one of the possible mechanisms for the effect of plantago major L on such conditions is the contractile property of smooth muscles such as vasoconstriction, which is resulted from some of its active compounds (Bazafkan et al, 2014;Nejati et al, 2018). Another mechanism that might be involved is the generation of reactive oxygen species (ROS) that modulate the expression and activity of angiogenic factors and signaling pathways (Asif et al, 2016;Entezari Heravi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the impact on Wistar rats’ local wound healing of an ointment made from a combination of cabbage, pomegranate, and Plantago major ethanolic extract found that on Days 3, 6, 9, and 12, the average percentage of wound healing in the various groups was as follows: In the control group, there were 21.3%, 37.87%, 67.39%, and 77.17%; in the positive control group, there were 24.98%, 34.21%, 70.74%, and 88.55%; and in the ointment group, there were 32.35%, 61.27%, 94.53%, and 99.91%. There was a noticeable difference between the control and main groups ( p < 0.05) [ 98 ]. The topical application of 10% Plantago major leaf extract (PMLE) to infected wounds in rabbits confirmed that PMLE plays a role in promoting healing.…”
Section: Wound-healing Effectsmentioning
confidence: 99%
“…In Romanian ethnopediatry, the plant leaves were considered to be beneficial against cough, oliguria, intestinal worms, trauma, and debility [75,86]. Modern studies provided some evidence for its wound healing [164,165], antibronchitis [166], anti-inflammatory [167,168], immunoenhancing [169], and antiparasitic potential [170]. On the contrary, one adult clinical study reported the lack of diuretic effect, which is claimed by various ethnomedical systems [171].…”
Section: Comparison Of Relative Therapeutic Versatility Of Top Medicimentioning
confidence: 99%